Rancang Bangun Sistem Informasi Pengarsipan dan Pendistribusian Surat - Tamam Asrori; Tyas Agustian Mahardika (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2022)
Archive management is very important for an institution. Archive management at Panca Marga University has not been done computerized. Manual management raises several problems, including slow search, need for extensive mail storage and rather slow distribution. These problems can be solved by building an information system for filing and distributing mail. System development use the waterfall method. In this study, a system can be built to be able to manage incoming letters, outgoing letters, decision letters, letter dispositions along with the distribution of the letters. Based on the results of black box testing, the system that was built was running according to its functionality.